Protein Content, Yield, and Taste of Beef Patty Containing Black Cumin (Nigella Sativa L.) and Different Parts of Meat - Nita, Nita; Hafid, Harapin; Rusdin, Muh. (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
Quality improvement protein content, yield and taste of beef patties can be improved by adding black cumin and using different parts of the meat. This research aims totest the effectinteraction of black cumin levels and different parts of the flesh on quality of protein content, yield and tastebeef patty, testing independent effects giving different kinds of black cumin to quality of protein content, yield and taste beef patty, testing independent effects use of different parts of meat against quality of protein content, yield and taste beef patty. This research used a Completely Randomized Design with a 5 x 3 Factorial pattern with a quality test for protein content and yield using 3 (three) replications and a taste test using 12 (twelve) replications. The first factor is the black cumin level of 0%, 0.5%, 1%, 1.5%, and 2%. The second factor is the parts of the meat, namely the sirloin, top side and shank. Research variables include protein content, yield, and taste. The results showed that the interaction of black cumin levels and different parts of the meat showed a significant influence (P0.05) on yield and taste values, the independent effect of giving different black cumin showed a significant effect (P0.05) on yield and taste values, and the independent influence of using different parts of meat had a significant effect (P0.05) on the taste value. It can be concluded from the research results that the best treatment combination is J4P2 (2% black cumin with top side meat).